Mengikis Budaya Patriarkhi-Domestic Melalui Pendekatan Pengkajian Islam Perspektif Gender - Husna Nashihin (Jurnal Ilmiah Citra Ilmu : Kajian Kebudayaan dan Keislaman, 2017)
The complexity of today’s contemporary world problems has an impact on the presence of new problems that are certainly waiting for the solution. Islam is a religion of rahmatan lil alamin. Consequently, Islam must be able to offer solutions to any problems that occur, one of the problems is gender. Therefore, a gender approach is needed to find the solution. Current the deviation of gender include stereotypes, subordination, marginalization, double burden, and violence. Deviation of gender is one of them caused by patriarchy-domestic culture. In addition, deviation of gender also occurs due to a false interpretation of the Qur’anic and Hadith texts related to gender. In carrying out an Islamic assessment a gender perspective should use the principle of a gender approach. First, the interpreter’s understanding sometimes becomes a subjective means of legitimacy. Second, interpretation results sometimes have the interest of the interpreter (factor of interest). Third, the general tendency in the meaning of text is literal meaning and ignores substantial meaning. The deeply rooted Patriarchal-Domestic culture within Indonesian society seems to be a major factor in deviation of gender. Therefore, the study of Qur’anic and Hadist texts needs to be done with a gender perspective.